Combined Platelet and Erythrocyte Salvage: Evaluation of a New Filtration-based Autotransfusion Device. (13th May 2021) - Mansour, Alexandre; Decouture, Benoit; Roussel, Mikaël; Lefevre, Charles; Skreko, Lucie; Picard, Véronique; Ouattara, Alexandre; Bachelot-Loza, Christilla; Gaussem, Pascale; Nesseler, Nicolas; Gouin-Thibault, Isabelle
Abstract : Background: The SAME device (i-SEP, France) is an innovative filtration-based autotransfusion device able to salvage and wash both red blood cells and platelets. This study evaluated the device performances using human whole blood with the hypothesis that the device will be able to salvage platelets while achieving a erythrocyte yield of 80% and removal ratios of 90% for heparin and 80% for major plasma proteins without inducing signification activation of salvaged cells. Methods: Thirty healthy human whole blood units (median volume, 478 ml) were diluted, heparinized, and processed by the device in two consecutive treatment cycles. Samples from the collection reservoir and the concentrated blood were analyzed. Complete blood count was performed to measure blood cell recovery rates. Flow cytometry evaluated the activation state and function of platelets and leukocytes. Heparin and plasma proteins were measured to assess washing performance. Results: The global erythrocyte yield was 88.1% (84.1 to 91.1%; median [25th to 75th]) with posttreatment hematocrits of 48.9% (44.8 to 51.4%) and 51.4% (48.4 to 53.2%) for the first and second cycles, respectively. Ektacytometry did not show evidence of erythrocyte alteration. Platelet recovery was 36.8% (26.3 to 43.4%), with posttreatment counts of 88 × 10 9 /l (73 to 101 × 10 9 /l) and 115 × 10 9 /l (95 to 135 × 10 9 /l) for the first and second cycles, respectively. Recovered platelets showed a low basal P-selectin expression at 10.8% (8.1 to 15.2%) and a strong response to thrombin-activating peptide. Leukocyte yield was 93.0% (90.1 to 95.7%) with no activation or cell death. Global removal ratios were 98.3% (97.8 to 98.9%), 98.2% (96.9 to 98.8%), and 88.3% (86.6 to 90.7%) for heparin, albumin, and fibrinogen, respectively. The processing times were 4.4 min (4.2 to 4.6 min) and 4.4 min (4.2 to 4.7 min) for the first and second cycles, respectively. Conclusions: This study demonstrated the performance of the SAME device. Platelets and red blood cells were salvaged without significant impact on cell integrity and function. In the meantime, leukocytes were not activated, and the washing quality of the device prevented reinfusion of high concentrations of heparin and plasma proteins. Abstract : A novel filtration-based autotransfusion device salvaged both red blood cells and platelets, without significantly impacting cell integrity and function, with the recovery of 88.1 and 36.8%, respectively. The filtration and washing prevented reinfusion of high concentrations of heparin and did not activate leukocytes. Supplemental Digital Content is available in the text.